Leadless pacemaker implantation after transcatheter aortic valve replacement. (19th May 2022) - Jelisejevas, J; Regoli, F; Hofer, D; Conte, G; Saguner, AM; Caputo, ML; Grazioli, L; Steffel, J; Auricchio, A; Breitenstein, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Impairment of the conduction system may occur in 9-30 % of patients undergoing transcatheter aortic valve replacement (TAVR). Since this is typically an elderly and frail patient population, leadless pacing potentially offers benefits over conventional transvenous pacemaker devices. However, available efficacy and safety outcome data of leadless pacing in a population who underwent a TAVR procedure is still limited. Purpose: Retrospective analysis of efficacy and safety outcome data in patients who underwent leadless pacemaker implantation after TAVR due to relevant bradycardias. Methods and Results: In this retrospective analysis from two large Swiss implantation centres, 257 consecutive patients undergoing leadless pacemaker were included. Of the total cohort, 26 subjects had a previous TAVR complicated by early (within 30 days)- or late-onset (after 30 days) bradycardias (Table 1). The TAVR group did not differ compared to the non-TAVR with regard to age, gender and left-ventricular ejection fraction (LVEF). Median duration between valve intervention and leadless pacemaker implantation was 8 days (range 0 to 368 days). After a TAVR procedure, left femoral access was chosen in 30.8% (8 of 26 of cases) for the leadless pacemaker implantation as compared to 5.2% (12 of 231 of the cases) in the remaining population (P < 0.01). Mean implantation duration was 56 ± 22 min in the TAVR group compared to 48 ± 20 min (P = NS) and a successful implantation rate of 100.0 % in the TAVR group vs 98.7% in the remaining population (P = NS). There were no significant differences in pacing parameters (sensing, impedance and threshold, respectively) between the two groups. A total of eight major periprocedural complications (3.1%) were encountered in the entire cohort within 30 days, of which one (pericardial effusion) occurred in the TAVR population (P = 0.04), which was managed conservatively with pericardiocentesis. Conclusions: Leadless pacemaker implantation appears to be safe and effective in patients after TAVR in need of antibradycardia pacing.